Developing an interregional input-output table for cross-border economies : an application to Lao People's Democratic Republic and Thailand - Sim, Benson; Secretario, Francisco; Suan, Eric; Asian Development Bank. Economics and Research Department (ERD statistical paper series, ISSN 1995-2996, 2007)
Abstract (s. vii).
Keywords: talouselämä : Thaimaa; talouselämä : Laos; rajakauppa : Thaimaa : Laos; taloudelliset mallit : Aasia